Uji Aktivitas Ekstrak Kloroform Daun Sangkareho (Callicarpa longifolia Lam.) terhadap Penyembuhan Luka Sayat pada Tikus Jantan Galur Wistar - Theresia Carolina; Dyan Fitri Nugraha; Umi Hanik Fetriyah (Jurnal Surya Medika (JSM), 2022)
Wounds that are not treated properly could lead to infections and the worst result would be death. Meanwhile, people in Central Kalimantan use the Sangkareho (Callicarpa longifolia Lam.) leaf as wound medicine without any scientific proof. The research aims to analyze the activity of chloroform extract of Sangkareho (Callicarpa longifolia Lam.) leaf on wound healing in male Wistar rats. This research used a true experimental method with a post-test-only control group design. The sample is 25 male Wistar rats that were randomly selected into 5 groups. Rats were wounded by a 10 mm incision wound with a depth of 2 mm in regio vertebralis thoracis and regio interscapularis. Data collection based on observed the incision for 10 days (changed in wound length and wound phase). Statistically, the analysis used the Kruskal Wallis test and Mann Whitney test. The result is chloroform extract of Sangkareho (Callicarpa longifolia Lam.) leaf dose 200 mg/200 g BW enter remodeling phase with wound length 0 mm on the sixth day faster than the positive control. The results of statistical data analysis show significant differences between chloroform extract of Sangkareho (Callicarpa longifolia Lam.) leaf dose 200 mg/200 g BW group and positive control group. Chloroform extract of Sangkareho (Callicarpa longifolia Lam.) leaf dose 200 mg/200 g BW group help wound healing faster than positive controls based on change on wound length and wound phase. Wound healing is suspected because of secondary metabolites in Sangkareho (Callicarpa longifolia Lam.) leaf.